THE SPIRITUAL CONSTRUCTION OF STUDENTS WITH DISABILITIES: A PHENOMENOLOGICAL STUDY OF RELIGIOUS EXPERIENCES AT THE TAMBAK BENING ISLAMIC BOARDING SCHOOL - eli masnawati (Atta'dib Jurnal Pendidikan Agama Islam, 2026)
This study aims to explore and describe the spiritual construction of students with disabilities at the Tambak Bening Islamic Boarding School in Surabaya. Using a qualitative, phenomenological approach, this study explores the subjective religious experiences of students with special needs in the Islamic boarding school environment. Data were collected through in-depth interviews, participant observation, and documentation of students with disabilities, teachers, and caregivers. Data analysis followed Moustakas' model, which encompasses epoche,  horizontalization, grouping of meanings, and the discovery of the essence of the phenomenon. The results indicate that the spirituality of students with disabilities is shaped by a dynamic interaction among personal circumstances (motivation and resilience), the inclusive socio-religious environment of the Islamic boarding school, and the ongoing process of spiritual development (tarbiyah ruhiyah). Religious experiences, such as inner peace through dhikr (remembrance of God) and a sense of acceptance within the community, shape God-consciousness, spiritual resilience, and self-acceptance. This study concludes that Islamic boarding schools play a strategic role as inclusive Islamic educational spaces that transform physical limitations into profound spiritual strength.